Physical activity for health and fitness - Jackson, Allen W. (Human Kinetics, 2004)
This revised edition provides all the features and benefits of the original edition plus updated nutritional information and references. 'Physical Activity for Health and Fitness' will help students make physical actitivy a priority today in the future.